(untitled) (diségno, 2021)
In the Church of St. Anastasia, in Verona, Italy, there is a fresco from Pisanello, dated between 1432 and 1438. It is named San Giorgio e la Principessa (St. George and the Princess), but it has received in time the final addition “of Trebisonda”. The vision depicted inside this fresco opens a reflection about interpretation and representation, about resolution and dissolution of reality. The work of representation can be a way of visualizing an idea or a place from which there is just a vision coming from the words of others. No matter how uncertain it is, the vision of the author leads to the definition of the result, capturing myths and fascinations, like ‘the East’, ‘the city far away’, ‘Trebisonda’, ‘the travel’. The traces inserted in the artwork may contain a specific code, later (mis)interpreted in a new cultural scenario. The idea of Pisanello depicting the city on the Black Sea is not supported by resolutive evidence. It seems like a weird alchemy pushing ideas. In this paper, a ‘state of the knowledge’ about this artwork will be the frame for a reflection about the visionary contents and elements in the main scene and in the background. A test operated with a group of architecture students and artists will investigate what happens when representing a city in a landscape seen only through oral communication. A graphic and logical matching between the ideal representation of the city in the fresco and the past and present Trebisonda/Trebizond/Trabzon will complete the analysis.